A Biosurfactant/Polystyrene Polymer Partition System for Remediating Coal Tar-Contaminated Sediment. Issue 6 (17th August 2016) - Wilton, Nicholas M.; Zeigler, Christian D.; Leardi, Riccardo; Robbat, Albert
ABSTRACT: A sustainable, green chemistry process is proposed for the cleanup of coal tar impacted sediment in under 2 hr. A mixture of proteins and polypeptides, extracted from corn gluten meal and hemp, when mixed with sediment and polystyrene foam pellets (PFPs), serves to mobilize tar, which sorbs onto PFP. Since the sorbent floats, coal tar is easily extracted from the agitation vessel. An empirically derived 4-dimensional surface response model accurately predicts removal rates of the tar and operational costs of the system under various experimental conditions. At optimum relative to cost, 81% of the two to six ring polycyclic aromatic hydrocarbons (PAHs) and 73% of the total tar mass are removed despite high sediment organic carbon content (16.4%) and silty fines (∼85%). Multiple PFP extractions ( n = 2) of the same sediment/biosurfactant mixture yielded 94% extraction of PAH. Scanning electron microscope images illustrate free-phase tar (globule) sorption onto the foam. A field pilot was conducted in which 25 kg of sediment was processed. Results were in excellent agreement with both lab (10 g) experiments and model predictions. The process is considered sustainable and green because the active ingredients are derived from renewable crop materials, recycled polystyrene is used, and the biosurfactant is recyclable which reduces water demand and treatment costs, with the recovered tar used as fuel and sediment as beneficial reuse material.